A novel inborn error of the coenzyme Q10 biosynthesis pathway: cerebellar ataxia and static encephalomyopathy due to COQ5 C‐methyltransferase deficiency. Issue 1 (8th November 2017) - Malicdan, May Christine V.; Vilboux, Thierry; Ben‐Zeev, Bruria; Guo, Jennifer; Eliyahu, Aviva; Pode‐Shakked, Ben; Dori, Amir; Kakani, Sravan; Chandrasekharappa, Settara C.; Ferreira, Carlos R.; Shelestovich, Natalia; Marek‐Yagel, Dina; et al.
Abstract: Primary coenzyme Q10 (CoQ10 ; MIM# 607426) deficiencies are an emerging group of inherited mitochondrial disorders with heterogonous clinical phenotypes. Over a dozen genes are involved in the biosynthesis of CoQ10, and mutations in several of these are associated with human disease. However, mutations in COQ5 (MIM# 616359), catalyzing the only C‐methylation in the CoQ10 synthetic pathway, have not been implicated in human disease. Here, we report three female siblings of Iraqi‐Jewish descent, who had varying degrees of cerebellar ataxia, encephalopathy, generalized tonic‐clonic seizures, and cognitive disability. Whole‐exome and subsequent whole‐genome sequencing identified biallelic duplications in the COQ5 gene, leading to reduced levels of CoQ10 in peripheral white blood cells of all affected individuals and reduced CoQ10 levels in the only muscle tissue available from one affected proband. CoQ10 supplementation led to clinical improvement and increased the concentrations of CoQ10 in blood. This is the first report of primary CoQ10 deficiency caused by loss of function of COQ5, with delineation of the clinical, laboratory, histological, and molecular features, and insights regarding targeted treatment with CoQ10 supplementation. Abstract : Malicdan, Vilboux, Ben‐Zeev, et al., describe a new primary coenzyme Q10 (CoQ10 ) deficiency due to loss‐of‐function mutations in COQ5 that encodes for an enzyme catalyzing the only C‐methylation in CoQ10 synthesis. Using whole genome sequencing, the authors have shown that a tandem duplication due to an unbalanced crossing‐over of AluY and AluYc led to the formation of a new isoform with an aberrant 3′UTR. Oral CoQ10 supplementation led to improvement of CoQ10 in the blood and subsequent clinical improvement.